An Analysis of Black Income in India - Aggarwal, Ritika (Indian Journal of Finance, 2017)
Black income comprises of a very significant and fast growing element of India's economy. The various social, political, and economic consequences of black operations are very serious and have already affected most walks of life and economic activities. This paper tried to explore the various types and sources of black income in India, in light of the current government schemes to control black income generation. Unlike other studies, it did not restrict itself to an examination of the evasion of personal income tax only, but covers a much wider territory, going from evasion of excise and custom duties to smuggling. It also provided rough estimates of black income over the period of mid-1950s to the present.